Rex Zero, the great pretender - Wynne-Jones, Tim. (New York : Farrar, Straus and Giroux, 2010)
In 1963, when his family moves across town to a new school district in Ottawa, Canada, twelve-year-old Rex conspires with best friends James, Kathy, and Buster to attend the school in his old neighborhood.
Sequel to: Rex Zero, king of nothing.
Keywords: Moving, Household -- Fiction; Schools -- Fiction; Friendship -- Fiction; Honesty -- Fiction; Family life -- Canada -- Fiction; Ottawa (Ont.) -- History -- 20th century -- Fiction; Canada -- History -- 1945- -- Fiction